Exercise intensity during an 8-day mountain bike marathon race - Wirnitzer, K. C.; Kornexl, E. (European Journal of Applied Physiology, 2008)
The purpose of this descriptive study was to examine the exercise intensity of a mountain bike (MTB) marathon race lasting 8 days. Seven amateur MTBers (age 33.6 ± 3.0 years, height 1.67 ± 0.5 m, body mass 58.4 ± 9.9 kg) completing the Transalp Challenge 2004 were involved in the study. Before the race subjects completed a maximal incremental cycling test to determine four intensity zones based on the heart rate (HR) corresponding to fixed blood lactate thresholds (2, 4 and 6 mmol/L). The exercise intensity during the Transalp Challenge 2004 was measured by using HR short telemetry systems. Mean HR was 85.4% of maximal HR during the race or 79.2% of laboratory determined maximum. Thirty-six percent of total race time was spent in the high and very-high intensity zones. The study showed that this MTB stage race is physiologically very demanding, heavily involving both the aerobic and anaerobic energy system.